The Relationship Between the Type of Parent's Work Towards the Occurrence of Speech Delay at the Grahahusada Gresik Hospital - Retna Gumilang; Noer Farakhin; Dwi Kartika Maharani (Universitas Malahayati Lampung, 2024)
ABSTRACT The child's ability to communicate begins with the social reactions that the child shows by responding to the presence of others. This study aims to determine which parental role variables are associated with the incidence of speech delay in children with special needs at Grahahusada Gresik Hospital. Analytical observational research with cross sectional approach. The population in the study was all children with special needs who were examined at the children's poly with complaints of delays in work. The variables studied in the study are; individual characteristics of children, Child Age Group, Caregivers and incidence of speech delay. Techniques in sampling with total sampling techniques and analyzed using the Chi Square test. It is known that the children in the study were dominated by male gender 71.8% with the age group of toddlers 83.3% and most of the children were cared for by their own biological mothers as much as 62.8%. known the results of the Chi Square test p-Value variable gender of children 0.073, age category of children 0.004, and Caregivers 0.108. Child age category is associated with the incidence of speech delay in children with special needs at Grahahusada Gresik Hospital. Keywords: Speech Delay, Children with Special Needs, Parents